Light-Front model of transition form-factors in heavy meson decay - de Melo, J. P. B. C. [UNESP]; Frederico, T. (Elsevier B.V., 2010)
Electroweak transition form factors of heavy meson decays are important ingredients in the extraction of the Cabibbo-Kobayashi-Maskawa (CKM) matrix elements from experimental data. In this work, within a. light-front framework, we calculate electroweak transition form factor for the semileptonic decay of D mesons into a pion or a kaon. The model results underestimate in both cases the new data of CLEO for the larger momentum transfers accessible in the experiment. We discuss possible reasons for that in order to improve the model.